Description of the immature female stages of Ceroplastes janeirensis (Gray) (Hemiptera: Coccidae) with a special reference to the development of the wax test - de Cássia C. Rosa, Keila; Peronti, Ana Lucia B. G.; Sousa-Silva, Carlos Roberto (Zootaxa, 2011)
This paper describes the nymphal development of Ceroplastes janeirensis (Gray), which develops its wax test differently to that currently known for other Ceroplastinae. Macroscopic and microscopic characters of the three immature female stages are described and illustrated for the first time. An identification key to the female instars is provided and a brief discussion is also included comparing their morphology with those of other Ceroplastinae.